1995
DOI: 10.1063/1.113924
|View full text |Cite
|
Sign up to set email alerts
|

Se chemical passivation and annealing treatment for GaAs Schottky diode

Abstract: A Se chemical passivation [(NH4)2S+Se] for GaAs Schottky diodes is presented. We have found that our (NH4)2S+Se passivated Schottky diodes have more than one order of magnitude higher forward current density than the (NH4)2Sx passivated ones. In rapid thermal annealing treatment, an initial decrease and then increase of forward current density for (NH4)2Sx passivated diodes is observed. For the (NH4)2S+Se and (NH4)OH treated diodes, a steady decrease of Schottky barrier height with increased annealing temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…Combined selenium and sulfur treatments have become popular, particularly use of SeS 2 , in an effort to exploit the beneficial effects of both kinds of atoms. , Kuruvilla et al identified a correlation between film thickness and PL efficiency, with the thinnest SeS 2 films producing the greatest PL intensities. On the basis of AFM studies, they attribute this observation to the existence of a well-ordered (1 × 1) adlayer, with a lattice period of 3.8 Å on the GaAs (100) surface. This value is close to that of ∼4 Å for the unreconstructed surface, and the nearly matched lattice parameters may be related to energetic stabilization of the GaAs surface through surface structural modification.…”
Section: Selenidesmentioning
confidence: 97%
“…Combined selenium and sulfur treatments have become popular, particularly use of SeS 2 , in an effort to exploit the beneficial effects of both kinds of atoms. , Kuruvilla et al identified a correlation between film thickness and PL efficiency, with the thinnest SeS 2 films producing the greatest PL intensities. On the basis of AFM studies, they attribute this observation to the existence of a well-ordered (1 × 1) adlayer, with a lattice period of 3.8 Å on the GaAs (100) surface. This value is close to that of ∼4 Å for the unreconstructed surface, and the nearly matched lattice parameters may be related to energetic stabilization of the GaAs surface through surface structural modification.…”
Section: Selenidesmentioning
confidence: 97%
“…Any mechanism that modifies the properties of the interface such as the introduction of an interfacial layer [1][2][3][4], annealing [5,6], irradiation with gamma rays [7,8], protons [9][10][11][12][13][14] and neutrons [14][15][16], ion implantation, [17][18][19] and high-energy ion beam irradiation [20][21][22][23][24][25][26] are found to alter the characteristics of the barrier. The Schottky barrier height (SBH) forms a very important parameter of the diode as it controls the electrical transport across the barrier.…”
Section: Introductionmentioning
confidence: 96%
“…Chalcogenide passivation seems to be one of the most promising means to solve this problem. Presently, the most commonly used is wet chemical GaAs surface modification by sulfides (especially sodium (Na 2 S Á 9 H 2 O) or ammonium ((NH 4 ) 2 S, (NH 4 ) 2 S x ) sulfides [4,5,8,9,10,15]). GaAs surface chalcogenide treatment can be performed by using vacuum deposition techniques (physical deposition of monolayers of elemental chalkogenides, or treatment in H 2 Se or H 2 S [1, 2, 11, 19 to 22], or using wet chemical chalcogenide treatment methods [3, 4 to 10, 14 to 18].…”
Section: Introductionmentioning
confidence: 99%
“…Schottky barrier height control [1 to 11] and surface recombination rate reduction [3, 12 to 18] were obtained in this way. But more effective for GaAs surface passivation seems to be Se treatment, because of its possible higher thermal stability and resistivity against oxidation [7,8,9,17,22]. Presently, the most commonly used is wet chemical GaAs surface modification by sulfides (especially sodium (Na 2 S Á 9 H 2 O) or ammonium ((NH 4 ) 2 S, (NH 4 ) 2 S x ) sulfides [4,5,8,9,10,15]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation